The Palgrave Handbook of African Women's Studies 2019
DOI: 10.1007/978-3-319-77030-7_160-1
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and Women’s Health in Africa

Abstract: Women's empowerment and its relationship with women's health in Africa is the focus of this chapter. Studies show that the higher the level of women's education and their economic empowerment, the more they are able to take independent decisions, including those that affect their individual health, as well as their capacity to contribute to the processes of making policies that affect them. Governments across Africa have not been proactive in addressing women's health issues, in spite of signing various intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The findings from this study indicated that a variation in the use of health facility delivery among women across the clusters of Ethiopia. In adjusted multilevel logistics regression, those women with a high empowerment index and living in the community where the most people encourage a health facility delivery were more likely to use a health facility during their delivery, these findings were consistent with other studies (20,21).…”
Section: Discussionsupporting
confidence: 89%
“…The findings from this study indicated that a variation in the use of health facility delivery among women across the clusters of Ethiopia. In adjusted multilevel logistics regression, those women with a high empowerment index and living in the community where the most people encourage a health facility delivery were more likely to use a health facility during their delivery, these findings were consistent with other studies (20,21).…”
Section: Discussionsupporting
confidence: 89%
“…The 2018 female HDI value for Congo was 0.591 in contrast with 0.635 for males, resulting in a Gender Development Index (GDI) value of 0.931, placing it into Group 3 [ 19 ]. Poor gender power relations is attributable to inequities across most African countries including the Republic of Congo, resulting to women’s inability to make the decision of having a safe abortion [ 20 , 21 ]. The Republic of Congo is on the WHO list of high burden countries for various health problems [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of them have resigned to their fate by accepting gender-based violence, gender discrimination and other forms of abuse as their lot (Amroussis et al, 2016). Until they are truly emancipated and empowered politically and economically to make free decisions relating to reproduction and reproductive health, women and girls cannot be said to fully enjoy their fundamental rights (Nmadu, 2010;Nwogwugwu, 2020).…”
Section: Health and Reproductive Rights Of Women And Girlsmentioning
confidence: 99%